Description of the twelfth species of the genus Thermistis Pascoe, 1867 (Coleoptera: Cerambycidae: Lamiinae: Saperdini) - Lin, Meiying; Tichý, Tomáš (Zootaxa, 2020)
Thermistis Pascoe, 1867 (Cerambycidae: Lamiinae: Saperdini) is a large and brightly coloured Oriental saperdine genus. It was thoroughly revised by Lin et al. (2012), with 11 species from the Oriental region. After that, only some new locality reports were added to this genus (Lin & Vives 2012).